The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3390/ma4040845
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Performance of Templated Silica Membranes in Non-Osmotic Desalination

Abstract: In this work we investigate the potential of a polyethylene glycol-polypropylene glycol-polyethylene glycol, tri-block copolymer as a template for a hybrid carbon/silica membrane for use in the non-osmotic desalination of seawater. Silica samples were loaded with varying amounts of tri-block copolymer and calcined in a vacuum to carbonize the template and trap it within the silica matrix. The resultant xerogels were analyzed with FTIR, Thermogravimetric analysis (TGA) and N2 sorption techniques, wherein it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 21 publications
2
12
0
3
Order By: Relevance
“…With increasing the carbon template (P123-20 and 35) concentration, the xerogels tended to form mesoporous materials with a higher adsorption saturation capacity above 0.35 p/p1 and a small degree of hysteresis. This results in an estimate of 25% increase in the surface area and pore volume with increasing P123 copolymer incorporation which is in good agreement with Ladewig et al [7] for similar sols, but prepared by the acid catalysed sol-gel method. Furthermore, when P123 concentration reached 50 wt%, it is clearly observed that the isotherm profiles are truly type IV isotherms and mesoporous as evidenced by their large extent of hysteresis near 0.5 p/p1 indicating the occurrence of capillary condensation.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…With increasing the carbon template (P123-20 and 35) concentration, the xerogels tended to form mesoporous materials with a higher adsorption saturation capacity above 0.35 p/p1 and a small degree of hysteresis. This results in an estimate of 25% increase in the surface area and pore volume with increasing P123 copolymer incorporation which is in good agreement with Ladewig et al [7] for similar sols, but prepared by the acid catalysed sol-gel method. Furthermore, when P123 concentration reached 50 wt%, it is clearly observed that the isotherm profiles are truly type IV isotherms and mesoporous as evidenced by their large extent of hysteresis near 0.5 p/p1 indicating the occurrence of capillary condensation.…”
Section: Resultssupporting
confidence: 87%
“…The high water fluxes coupled with consistent excellent salt rejections ( 499.5%) clearly indicate that the performance of the base catalysed silica membrane containing carbon moieties derived from P123 triblock copolymers is beyond the state of art. For instance, the water flux of 2.5 kg m À 2 h À 1 and salt rejections 4 99.8% of base catalysed P123-50 silica membranes at room temperature for a sea water with NaCl concentration of 3.5 wt% are comparable or even better than those reported in the literature for acid catalysed silica membranes prepared with hexadecyl trimethyl ammonium bromide surfactant (1.9 kg m À 2 h À 1 and 94%) [10], methyl tri-ethoxy silane and TEOS (1.7 kg m À 2 h À 1 and 95%) [8], triblock copolymer templated silica membranes (3.0 kg m À 2 h À 1 ; 97%) [7]. When compared to the performance of the cobalt oxide silica membranes [33], the water fluxes produced by the membranes in this work are at least 300% (P123-5) to 800% (P123-50) higher yet with similar salt rejections, irrespective of the feed salt concentration and temperature.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, as shown in this study that the carbon matrix offers the fine-tuning of porosity and pore volume, which are extremely important for determining water flux of the hollow fibers for water production as membranes. This is exemplified by numerous studies of microporous ceramic membranes for desalination [59][60][61] and alcohol pervaporation [62][63][64]. On the other hand, highly mesoporous membranes, although lead to a high water production, will fail to separate the solute from water due to pore-wetting effect [39,65].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental set-up included a feed vessel, peristaltic pump, membrane module, condenser unit, vacuum pump and data logging system connected to computer. 35 Despite the appearance of several smaller peaks and shoulders, the main exothermic peak at ~350 °C is sharp and narrow. The feed was introduced into membrane module at a flow rate of 5 L h -1 and circulated back into the feed vessel.…”
Section: Test Of Membrane Performance In Water Desalinationmentioning
confidence: 98%